The eneolithic necropolis of Forlì-Celletta dei Passeri: taphonomy, anthropology and paleonutrition (Journal of Biological Research - Bollettino della Società Italiana di Biologia Sperimentale, 2012)
-
Keywords: copper age; necropolis; paleobiology; paleonutrition